Attitudinal Explanation on Virtual Shopping Intention - Ritzky Karina M.R. Brahmana; Rayenda Khresna Brahmana (Asian Journal of Technology Management, 2014)
Abstract. Virtual stores provide great efficiency in the retail value chain, and their existence has tremendously paved the way for electronic commerce. Understanding the intention of consumers to shop online in attitudinal perspective will provide important contribution to the area of e-commerce. This research proposes Task Technology Fit, Perceived Ease of Use (PEoU), and Perceived Usefulness (PU) as the factors that drive consumers’ intention. The results from our survey study of 310 online consumers in Indonesia indicate that TTF affects PEoU and PU significantly. Our hierarchical model also reports that PEoU is the mediating effect on the relationship between TTF and Intention. The resulting model explains a large portion of the factors that lead a user’s behavioural intention to use a virtual shop.   Keywords : Attitudinal, Task Technology Fit, Perceived Ease of Use, Perceived Usefulness, Retail, Virtual Shopping Intention